Polarization is the psychological foundation of collective engagement - Laura G. E. Smith; Emma F. Thomas; Ana-Maria Bliuc; Craig McGarty (Communications Psychology, 2024)
Abstract The term polarization is used to describe both the division of a society into opposing groups (political polarization), and a social psychological phenomenon (group polarization) whereby people adopt more extreme positions after discussion. We explain how group polarization underpins the political polarization phenomenon: Social interaction, for example through social media, enables groups to form in such a way that their beliefs about what should be done to change the world—and how this differs from the stance of other groups—become integrated as aspects of a new, shared social identity. This provides a basis for mobilization to collective action.